(untitled) (Journal of history, 2017)
This article examines the medieval social structure of the Turkic tribes of Central Asia, including the continuity of the titles of Turkic tribes rulers. The title of rulers of the Turkic tribes and tribal associations "qagan" was later transferred as the defining name of all the population belonging to this tribe and they were called kaganates. Also, in honor of Qagan, in accordance with achievements and committed heroic deeds, were given several titles, for example, among the rulers of the Western Turkic Kaganate, in addition to their own names, there were several titles: Sy-zhabgu Khan Tolys-tegin, Irbis Yshbara (631-633), Ishbara-Tolys-shad Khan (634-639), Hallyk Yshbara-Zhabgu Khan (653-657) and others. Over time, the titles of the rulers of the Turkic khanate, Western and Eastern Turkic Kaganate, Turgesh, Uigur, Kyrgyz, and Karluk Khaganates had changed, but their main activities had been preserved. In addition, based on the Chinese and Arab sources, the main twenty-eight titles of Turkic tribes were identified and a comparative analysis was made. As a result, the author concludes that, in the VII-XII centuries, the titles of the Turkic tribes of Central Asia had a coherent order of continuity.